2017
DOI: 10.3390/jcs1010008
|View full text |Cite
|
Sign up to set email alerts
|

Fused Deposition Modelling of Natural Fibre/Polylactic Acid Composites

Abstract: Abstract:Fused deposition modelling is a simple additive manufacturing technology utilising fine filament extrusion of predominantly thermoplastic materials to build 3D objects layer by layer. This research explores the feasibility and the factors involved in using fused deposition modelling to produce natural fibre reinforced composite components. Uniform 3-mm filaments of both hemp and harakeke (Phormium tenax) in varying weight percentages within polylactic acid (PLA) polymer were successfully produced and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 20 publications
2
54
0
1
Order By: Relevance
“…Although there are quite a few studies on PLA-based biocomposites in FDM, the challenges brought by the material coupled to the ones coming from the processing method have forced a “trial and error” procedure. Interestingly, the available literature that does not make use of commercial filaments is significant [3,9,17,21,23,38,39,45,46,48,49,65,66,67,68], but has appeared only recently and the effects of processing parameters, additives formulation, patterning and geometrical features are not yet deeply explored. As can be seen from Table 3, plasticizers [21,45,48], toughening agents [39,65] and compatibilizers [39] have been studied.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are quite a few studies on PLA-based biocomposites in FDM, the challenges brought by the material coupled to the ones coming from the processing method have forced a “trial and error” procedure. Interestingly, the available literature that does not make use of commercial filaments is significant [3,9,17,21,23,38,39,45,46,48,49,65,66,67,68], but has appeared only recently and the effects of processing parameters, additives formulation, patterning and geometrical features are not yet deeply explored. As can be seen from Table 3, plasticizers [21,45,48], toughening agents [39,65] and compatibilizers [39] have been studied.…”
Section: Methodsmentioning
confidence: 99%
“…From Table 3 it is evident that the majority of the papers concerned with the tensile properties of FDM printed biocomposites dealt with PLA-based filaments [3,9,12,21,22,24,38,39,45,49,67,68,69,72,73,74]. These possess average tensile strength ranging from 20 up to 40 MPa, Young’s moduli between 2 and 3 GPa and elongation at break between 1.5% and 10%.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…σ S /σ S0 (%) = −74 + 0.32 × T P (C); R 2 = 0.96 (10) ε R /ε R0 (%) = −69 − 0.07 × T P (C); R 2 = 1.00 (11) Figure 10 compares the mechanical results of the present study with data reported from the literature and from the own authors experiments on different feedstock materials [8,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The performance of PLA is found among the top ranked materials.…”
Section: Mechanical Behaviourmentioning
confidence: 69%